Nanossistema agrícola para controle de doenças de plantas em soja e milho - Azevedo, Roberta Graciela Nogueira Guimarães (2023)
The incidence of phytopathogens is among the main factors that can affect crop productivity. Thus, the objective of this study is to use a nanosystem, previously selected and characterized, used alone or in conjunction with fungicides, with the aim of improving management performance and increasing the yield of soybean and corn crops. The soybean crop experiment was carried out in the 2021/2022 harvest, in Sorriso/MT and Ipiaçu/MG. The experimental design used was a randomized block, with six replications. The treatments employed were: T1: Control, T2: Nanoemulsion, T3: Fungicide, T4: Fungicide + agProtect, T5: Nanoemulsion + Fungicide and T6: Nanoemulsion + Fungicide + agProtect. For the corn crop, the experiment was carried out in the second harvest of 2021/2022, in Sorriso/MT and the experimental design used was a randomized block, with five replications. The treatments employed were: T1: Fungicide, T2: Fungicide + Nanoemulsion, T3: Fungicide + agProtect T4: Fungicide + Nanoemulsion + agProtect. The variables analyzed were disease severity index, Area Under the Disease Progression Curve (AUDPC), relative control efficacy, incidence of phytopathogens in seeds and grain yield analysis. Comparisons of means were analyzed using the Scott-Knott test at a 5% probability level, using the RBio software. The nanoemulsion proved to be stable, presenting a monomodal profile, without the presence of microparticles after 30 days of its development. For the soybean crop, the treatments that associated the use of agProtect, nanoemulsion or both with the application of fungicide, had lower severity in all evaluations, lower AUDPC, greater control efficacy in relation to the control and lower incidence of pathogens in the seeds in relation to treatments using fungicides. Regarding productivity, in the experiment at Ipiaçu-MG, the use of isolated nanoemulsion showed better crop yield. Similarly, the use of the nanoemulsion was able to improve the performance of fungicide management in the control of Bipolaris maydis in maize. Even in a situation of low disease pressure, the formulation contributed to reducing the severity and increasing the productivity of the crop. Based on the results, the use of the nanoemulsion was able to improve the performance of pathogen control management in soybean and corn crops